(untitled) - Minoli, Daniel (New Jersey, 2006)
This book provides a unique and thought-provoking perspective on how nanotechnology is poised to revolutionize the telecommunications, computing, and networking industries.
Keywords: Telecommunication,Computer networks,Nanotechnology; Equiment and supplies,Equiment and supplies